94.9k views
1 vote
Use the table for each problem to find the given limits.

Use the table for each problem to find the given limits.-example-1

1 Answer

5 votes

Answer:

1)
\lim_(x \to3 ) (2f(x))+g(-x))=13

2)
\lim_(x \to3 )(g(x))/(f(-x))=1/2

Explanation:

So we are given the limits:


\lim_(x \to3 )f(x)=4\text{ and } \lim_(x \to-3 ) f(x)=2

And:


\lim_(x \to 3 ) g(x)= 1\text{ and } \lim_(x \to -3 ) g(x)=5

Question A)

We have the limit:


\lim_(x \to3 ) (2f(x))+g(-x))

We can split this limit using our properties:


= \lim_(x \to 3) (2f(x))+\lim_(x \to 3) g(-x)

Now, use direct substitution. Substitute 3 for x. So:


=2(f(3))+g(-3)

We are given that f(3) (or the limit as x approaches towards 3) is 4.

We know that the limit as x tends towards -3 of g(x) is 5. In other words, g(-3) can be said to be 5. So:


=2(4)+(5)

Multiply:


=8+5=13

So, our limit is:


\lim_(x \to3 ) (2f(x))+g(-x))=13

Question B:

We have the limit:


\lim_(x \to3 )(g(x))/(f(-x))

Again, we can rewrite this as:


(\lim_(x \to3 )g(x))/(\lim_(x \to3 )f(-x))}

Direct substitution:


=(g(3))/(f(-3))

The value in the numerator, as given, is 1.

The value in the denominator will be 2. So:


=1/2

Therefore, our limit is:


\lim_(x \to3 )(g(x))/(f(-x))=1/2

And we're done!

User Bala Karthik
by
4.8k points